DAMPAK PENGUNGKAPAN LABA RUGI KOMPREHENSIF PADA PENGARUH KINERJA KEUANGAN TERHADAP REAKSI PASAR - Puspitasari, Rosaliani; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the impact of the disclosure of comprehensive profit-loss in the influence of financial performance to the market reaction. The financial performance is measured by cost of capital, earnings quality, and profitability. The population of this research is the entire companies which are listed in Indonesia Stock Exchange. The sample collection technique has been done by using purposive sampling. Based on the determined criteria, 40 property and real estate companies in 2012-2014 periods have been selected as samples. The research data is the secondary data which has been retrieved from Indonesia Stock Exchange and Indonesian Capital Market Directory i.e. the financial data in 2012-2014 periods. The hypothesis test of this research has been done by using multiple linear regressions analysis technique with SPSS application. The results showed that the cost of capital has negative effect to the market reaction and profitability has positive effect to the market reaction while the earnings quality has no effect to the market reaction as well as the disclosure of comprehensive income as the moderating variable has no impact on the effect of capital costs, earnings quality, and profitability of the market reaction.Keywords: capital cost, profit quality, profitability, market reaction, the disclosure of comprehensiveprofit-loss